Главная

Математика 6 класс И.И.Зубарева, А.Г.Мордкович

ГДЗ учебник по математике 6 класс И.И.Зубарева, А.Г.Мордкович

авторы: , .
издательство: "Мнемозина" 2014 год

Раздел:

Номер №789

Выполните действия:
а)
$(4\frac{7}{12} - 5\frac{3}{4}) : (\frac{7}{36} - 1\frac{1}{6})$
;
б)
$\frac{3}{8} : \frac{5}{12} - 3\frac{1}{2} * \frac{2}{5} + 1 : 3\frac{1}{3}$
;
в)
$1\frac{1}{4} * (-2\frac{2}{3}) + \frac{4}{5} * 2\frac{11}{12} - 1\frac{1}{6} : \frac{21}{22}$
;
г)
$\frac{3}{4} : (\frac{1}{14} - \frac{5}{7}) + (\frac{5}{6} - \frac{7}{12}) * 6\frac{2}{3}$
;
д)
$(2\frac{3}{11} - 1\frac{3}{22}) * (3\frac{1}{7} + 5\frac{1}{2})$
;
е)
$\frac{15}{37} * 1\frac{7}{30} - 1\frac{29}{48} * 1\frac{1}{63}$
.

Решение а

$(4\frac{7}{12} - 5\frac{3}{4}) : (\frac{7}{36} - 1\frac{1}{6}) = (4\frac{7}{12} - 5\frac{9}{12}) : (\frac{7}{36} - 1\frac{6}{36}) = -1\frac{2}{12} : (\frac{7}{36} - \frac{42}{36}) = -1\frac{1}{6} : (-\frac{35}{36}) = \frac{7}{6} * \frac{36}{35} = \frac{1}{1} * \frac{6}{5} = 1\frac{1}{5}$

Решение б

$\frac{3}{8} : \frac{5}{12} - 3\frac{1}{2} * \frac{2}{5} + 1 : 3\frac{1}{3} = \frac{3}{8} * \frac{12}{5} - \frac{7}{2} * \frac{2}{5} + 1 : \frac{10}{3} = \frac{3}{2} * \frac{3}{5} - \frac{7}{1} * \frac{1}{5} + \frac{3}{10} = \frac{9}{10} - \frac{7}{5} + \frac{3}{10} = \frac{9}{10} - \frac{14}{10} + \frac{3}{10} = -\frac{2}{10} = -0,2$

Решение в

$1\frac{1}{4} * (-2\frac{2}{3}) + \frac{4}{5} * 2\frac{11}{12} - 1\frac{1}{6} : \frac{21}{22} = \frac{5}{4} * (-\frac{8}{3}) + \frac{4}{5} * \frac{35}{12} - \frac{7}{6} * \frac{22}{21} = \frac{5}{1} * (-\frac{2}{3}) + \frac{1}{1} * \frac{7}{3} - \frac{1}{3} * \frac{11}{3} = -\frac{10}{3} + \frac{7}{3} - \frac{11}{9} = -\frac{30}{9} + \frac{21}{9} - \frac{11}{9} = -\frac{20}{9} = -2\frac{2}{9}$

Решение г

$\frac{3}{4} : (\frac{1}{14} - \frac{5}{7}) + (\frac{5}{6} - \frac{7}{12}) * 6\frac{2}{3} = \frac{3}{4} : (\frac{1}{14} - \frac{10}{14}) + (\frac{10}{12} - \frac{7}{12}) * \frac{20}{3} = \frac{3}{4} : (-\frac{9}{14}) + \frac{3}{12} * \frac{20}{3} = \frac{3}{4} * (-\frac{14}{9}) + \frac{1}{3} * \frac{5}{1} = \frac{1}{2} * (-\frac{7}{3}) + \frac{5}{3} = -\frac{7}{6} + \frac{10}{6} = \frac{3}{6} = \frac{1}{2}$

Решение д

$(2\frac{3}{11} - 1\frac{3}{22}) * (3\frac{1}{7} + 5\frac{1}{2}) = (2\frac{6}{22} - 1\frac{3}{22}) * (3\frac{2}{14} + 5\frac{7}{14}) = 1\frac{3}{22} * 8\frac{9}{14} = \frac{25}{22} * \frac{121}{14} = \frac{25}{2} * \frac{11}{14} = \frac{275}{28} = 9\frac{23}{28}$

Решение е

$\frac{15}{37} * 1\frac{7}{30} - 1\frac{29}{48} * 1\frac{1}{63} = \frac{15}{37} * \frac{37}{30} - \frac{77}{48} * \frac{64}{63} = \frac{1}{1} * \frac{1}{2} - \frac{11}{3} * \frac{4}{9} = \frac{1}{2} - \frac{44}{27} = \frac{27}{54} - \frac{88}{54} = -\frac{61}{54} = -1\frac{7}{54}$